PELAKSANAAN MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR ISLAM TERPADU ANDALAS CENDIKIA DHARMASRAYA - Marsusuanto Marsusuanto (IAIN Batusangkar, 2016)
This study focused on the implementation of learning management at Islamic Integrated Primary School Andalas Cendikia Dharmasraya. The qualitative approach was used in this study by applying interview and documentation as instruments. The findings revealed that the school had done the function of management. The school implemented Islamic culture such greeting to teachers and friends, kissing teachers’ hand when they shake hand and praying Dhuha together. The school had also made syllabus and lesson plan before instructional process.Keywords: Management, Learning, Islamic Integrated Primary School